HUMAN DIGNITY, HUMAN RIGHTS AND TORTURE - Wolbert, Werner (Scriptura, 2007)
In its first, fundamental sense, human dignity means something that is given, that cannot be lost, something to be respected. The human person has dignity simply because she is capable of morality. .....